2013
DOI: 10.1089/vim.2012.0068
|View full text |Cite
|
Sign up to set email alerts
|

Neuromyositis Associated with Cytomegalovirus Infection in an Immunocompetent Patient with Antineutrophil Cytoplasmic Antibodies-Associated Vasculitis

Abstract: The role of CMV in ANCA-positive vasculitis is controversial. A 40-year-old man, with an unremarkable medical history, presented with progressive muscle weakness of all four limbs, accompanied by diffuse myalgia, arthralgia, and a 10 kg weight loss 2 months before admission to the Neurology Department of our hospital. Clinical examination revealed a flaccid tetraparesis with absent reflexes on the lower limbs and marked muscle atrophy. Electrophysiological investigations were consistent with a demyelinating mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…CMV is a major opportunistic pathogen in immunosuppressive people. A case study found that biopsy muscle samples of neuromyositis patients were found to be positive for CMV staining (Oumerzouk et al, 2013). In addition to cancer, studies have shown that viral infections are associated with mild myopathies.…”
Section: Cytomegalovirus and Muscle Cancermentioning
confidence: 99%
“…CMV is a major opportunistic pathogen in immunosuppressive people. A case study found that biopsy muscle samples of neuromyositis patients were found to be positive for CMV staining (Oumerzouk et al, 2013). In addition to cancer, studies have shown that viral infections are associated with mild myopathies.…”
Section: Cytomegalovirus and Muscle Cancermentioning
confidence: 99%